2021
DOI: 10.1016/j.jbc.2021.101044
|View full text |Cite
|
Sign up to set email alerts
|

SRC3 acetylates calmodulin in the mouse brain to regulate synaptic plasticity and fear learning

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…28 In previous studies, we demonstrated that SRC3-mediated CaM acetylation was important for CaMKIIα activity and hippocampus-dependent memory in mice. 31,45,46 Here, we showed that HDAC9-mediated CaM deacetylation and CaMKIIα activity are severely abnormal in AD mouse brain.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…28 In previous studies, we demonstrated that SRC3-mediated CaM acetylation was important for CaMKIIα activity and hippocampus-dependent memory in mice. 31,45,46 Here, we showed that HDAC9-mediated CaM deacetylation and CaMKIIα activity are severely abnormal in AD mouse brain.…”
Section: Discussionmentioning
confidence: 77%
“…While total CaM, CaMKIIα, GluR1, and PSD95 did not change significantly in WT and APP/PS1 mice (Figure 2A,E–H,J,N–Q). In previous studies, we identified that SRC3 was the CaM acetyltransferase, and revealed that CaM acetylation was necessary for CaMKIIα activation 31,45,46 . We studied whether decreased CaM acetylation is caused by reduced SRC3, and found that SRC3 did not change significantly in APP/PS1 mice, compared to WT mice (Figure 2A,I,J,R).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the central nervous system, activation of NMDA receptors on the postsynaptic membrane leads to an increase in the local concentration of postsynaptic Ca 2+ , which binds to and activates CaM. Activated CaM activates Ca 2+ /CaM-dependent CaMKII, which plays an important role in synaptic plasticity, learning, and memory ( Zhang et al, 2021 ). KN-93 is a CaMKII inhibitor, which reduces the expression level and activity of CaMKII, as well as the phosphorylation level of its phosphorylation site Thr 305 ( Munevar et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many extracellular signals, such as neurotransmitters and hormones, regulate Ca 2+ content after interacting with receptors on cell membranes. Ca 2+ activates protein phosphatase and participates in synaptic plasticity regulation ( Roche et al, 1993 ; Zhang et al, 2021 ). As a result, we also investigated the mechanism, by which androgens affect synaptic protein PSD95 in HT22 cells through the Ca 2+ -induced Ca 2+ /CaMKII signaling pathway, and provided evidence for the neuroprotective effect of androgens.…”
Section: Introductionmentioning
confidence: 99%